2018
DOI: 10.7161/omuanajas.309644
|View full text |Cite
|
Sign up to set email alerts
|

Doğal florada kendiliğinden yetişen sarıçiçekli gazal boynuzu (Lotus corniculatus L.) ve dar yapraklı gazal boynuzu (Lotus tenuis Waldst.&Kit.) türlerinin toprak tercihleri, komşu bitkileri ve yem değerleri

Abstract: Doğal florada yetişen sarıçiçekli gazal boynuzu (Lotus corniculatus L.) ve dar yapraklı gazal boynuzunun (Lotus tenuis Waldst. & Kit.) toprak tercihleri, komşu bitkileri ve yem değerleri

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A total of 23 rangeland communities evaluated in Experiment 2 were separated to two rangeland classes subjected to SSG (100% cattle) or MSG (11.40% sheep, 4.06% goats and 84.58% cattle) system throughout the year for a long time. The frequency of each species was calculated as described by Khojasteh et al (2013) and Uzun and Ocak (2018). The BC of the rangelands is classified according to families (grass, legume and the others) and responses to grazing (decreaser, increaser and invader) of plant species (Koc and Kadioglu, 2012).…”
Section: Experiments IImentioning
confidence: 99%
“…A total of 23 rangeland communities evaluated in Experiment 2 were separated to two rangeland classes subjected to SSG (100% cattle) or MSG (11.40% sheep, 4.06% goats and 84.58% cattle) system throughout the year for a long time. The frequency of each species was calculated as described by Khojasteh et al (2013) and Uzun and Ocak (2018). The BC of the rangelands is classified according to families (grass, legume and the others) and responses to grazing (decreaser, increaser and invader) of plant species (Koc and Kadioglu, 2012).…”
Section: Experiments IImentioning
confidence: 99%
“…Recently, Aydin et al (2019) showed that although the nutritive values of rangeland species during growth stages were different, and forage qualities of species related to Poaceae and other botanical families were higher than those of the family Poaceae. There is a unique function of invasive species such as increasing productivity in overgrazed rangeland compared to native species, depending on grazing intensity and topography such as aspect and elevation (Eviner et al, 2012;Allen et al, 2017;Uzun et al, 2018). As such, in livestock production systems based on the exploitation of rangelands, farmers should be aware of floristic features (FF) of the most basic rangeland forages.…”
Section: Introductionmentioning
confidence: 99%
“…Farmers then make choices on which of the forage species are best suited based on quality and animal acceptance criteria (Sayar et al, 2015;Rouquette, 2016). The FF of rangeland forages are sorted as family of forage (Poaceae, Poaceae and other botanical families), preference by grazers (preferred and nonpreferred), growth form (annual and perennial) and response (decreasers, increasers and invaders) to grazing (Khojasteh et al, 2013;Uzun and Ocak, 2018). Forages with similar FF have a competitive interaction while species with different FF show a facilitative interaction (Khojasteh et al, 2013;Erkovan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%